Предмет: Алгебра,
автор: Angel6666666666666
Заранее спасибо)) Вычислите:
Приложения:
Ответы
Автор ответа:
1
Этот пример решается с помощью формулы сокращенного умножения
a^2 - b^2 = (a-b)(a+b)
53,6^2 - 53,5^2 = (53,6 - 53,5)(53,6 + 53,5) = 0,1 * 107,1 = 10,71
Ответ: 10,71
Автор ответа:
1
(((((((((((((((((((((((
Приложения:
Похожие вопросы
Предмет: Математика,
автор: rimmashul
Предмет: Русский язык,
автор: rrfgedstg
Предмет: Алгебра,
автор: marinadidenko300
Предмет: Физика,
автор: valshevskiy
Предмет: Математика,
автор: DickTator2009